Potency Nannochloropsis sp. As An Agent Bioremediation of Lead Heavy Metal (Pb) In Rivers Jenes - Shafira, Riannisa’a; Choirunnisa , Dhiya’; Pratiwi, Endah; Saputra, Alanindra (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The study aims to test the bioremediation potential of Nannochloropsis sp. against Pb (lead) contamination in the batik textile industrial area. The steps in this study include collecting river water samples from 3 different stations, preparing the samples by adding HNO3, culturing Nannochloropsis sp. seed for 7 days, testing the initial Pb metal content before and after treatment with Nannochloropsis sp. using wet-digestion techniques, and analyzing the samples. The water samples were taken from upstream, midstream, and downstream. The water samples were then preserved with HNO3. After that, Nannochloropsis sp. cultures were conducted, and results showed an increase in algal population after 7 days. Subsequently, metal content testing was conducted using AAS (Atomic Absorption Spectrophotometer) with a wet-digestion technique to eliminate organic substances in the samples from each station. Metal content testing was conducted before and after treatment with algae. The results of this study showed a decrease in Pb metal levels at each station in the Jenes River after treatment with algae and 7 days of culture. The average decrease obtained was 14.0 before treatment and 5.0 after treatment. Nannochloropsis sp. is an important bioremediation agent for degrading Pb (lead) contamination in river water resulting from excessive industrial waste. These findings contribute to the development of waste treatment to preserve the river ecosystem.